Changes in haematological parameters and iron metabolism associated with a 1600 kilometre ultramarathon - Fallon, K. E.; Sivyer, G.; Sivyer, K.; Dare, A. (British Journal of Sports Medicine, 1999)
OBJECTIVE: To investigate haematological variations and iron related changes in the serum of participants in a 1600 kilometre ultramarathon run. PARTICIPANTS: Seven male and two female participants in a 1600 km foot race. METHODS: Blood samples were obtained from the participants before, after four and 11 days of running, and at the end of the event. Samples were analysed by standard methods for haemoglobin, packed cell volume, total red cell count, mean red cell volume, mean red cell haemoglobin, total white cell count and differential, platelets, reticulocytes, iron, ferritin, total iron binding capacity, percentage transferrin saturation, haptoglobin, and bilirubin and corrected for changes in plasma volume. RESULTS: The following variables decreased during the event (p < 0.05): haemoglobin, packed cell volume, mean red cell volume, percentage lymphocytes, percentage monocytes, serum iron, total iron binding capacity, and percentage transferrin saturation. Increases (p < 0.05) were found in plasma volume, total red cell count (day 4 only), total white cell count, percentage and absolute numbers of neutrophils and reticulocytes, absolute numbers of lymphocytes and monocytes (day 4 only), absolute numbers of eosinophils (day 11 and race end), absolute numbers of basophils (race end only), platelets, ferritin, haptoglobin, and bilirubin (day 4 only). CONCLUSION: Ultramarathon running is associated with a wide range of changes in haematological parameters, many of which are related to the normal acute phase response to injury. These should not be confused with indicators of disease.